Genomic Characterization of Aureimonas altamirensis C2P003—A Specific Member of the Microbiome of Fraxinus excelsior Trees Tolerant to Ash Dieback - Regina Becker; Kristina Ulrich; Undine Behrendt; Volker Schneck; Andreas Ulrich (Plants, 2022)
Some European ash trees show tolerance towards dieback caused by the invasive pathogen Hymenoscyphus fraxineus. The microbiome of these trees harbours a range of specific bacterial groups. One of these groups belonging to the species Aureimonas altamirensis was studied in detail by genome analysis and a plant inoculation trial. The strain group was shown to be phylogenetically distinct from clinical isolates by 16S rRNA analysis and phylogenomics. Genome analysis of a representative strain C2P003 resulted in a large number of unique gene sequences in comparison to other well-studied strains of the species. A functional analysis of the genome revealed features associated with the synthesis of exopolysaccharides, protein secretion and biofilm production as well as genes for stress adaptation, suggesting the ability of C2P003 to effectively colonize ash leaves. The inoculation of ash seedlings with C2P003 showed a significant positive effect on the plant health of the seedlings that were exposed to H. fraxineus infection. This effect was maintained over a period of three years and was accompanied by a significant shift in the bacterial microbiome composition one year after inoculation. Overall, the results indicate that C2P003 may suppress H. fraxineus in or on ash leaves via colonization resistance or indirectly by affecting the microbiome.